Integration of Business Intelligence and Knowledge Management as a Strategic Intelligence Tool - Adirekpullap, Teerachai (2008)
The increasing competition in business forces enterprises to better concern customer satisfaction in terms of quality of products and services to gain sustainable competitive advantage. Achieving that goal requires uniform of applications and coordinating workflow which can be obtained through the integration of business intelligence (BI) and knowledge management (KM). Integration of BI and KM will provide harmonious tool for enterprise to exploit valuable information and knowledge and gain sustainable competitive advantage. This report aims to discuss and evaluate BI and KM framework to develop a practical BIKM framework. Literatures mention many advantages of implementing each technology and also advocate the trend of BIKM integration. The success of improving customer experience from BI and KM implementation derived from BT case study are analysed and discussed. There are some common elements of these two technologies shown in BT's good practices which then are drawn to develop common BIKM framework. Therefore the development of BIKM framework then is based on what BT has been done with some adjustments for generic purpose.